Macroconidia of Dermatophytes Fungi on Direct Microscopic Examinations - Putu Ayu Sisyawati Putriningsih; I Putu Gede Yudhi Arjentinia (Journal of Veterinary and Animal Sciences, 2017)
Dermatophytosis (ringworm) caused by dermatophytes fungi is one of the cattle diseases that can infect Bali cattle. Ringworm significantly cause economic loss to farmers and at the same time is zoonotic disease. Diagnosing dermatophytosis based on the clinical signs in the animals, followed by direct microscopic examination of skin scrapings and hair samples and confirmed by laboratory tests. On direct microscopic examination of skin scrapings and hair samples, generally detected the elements of the fungi such as arthrospores or hyphae. In this study, skin scrapings and hair samples from Bali cattle that clinically suffered ringworm were collected. Samples were then placed on an object glass, added drops of 10% KOH, covered with a cover glass, and after 10-15 minutes were examined under a microscope with a magnification of 100X and 400X. We were able to detect macroconidia as well as arthrospores of the fungi. Macroconidia were detected on two of seven samples tested (28.57%). Normally, macroconidia will not be detected prior culturing on agar media and staining with Lactophenol Cotton Blue (LPCB). Dermatophytes fungi produces two types of asexual propagule: the saprophytic conidia and parasitic conidia, depending on the environment where they grow. Macroconidia that were detected in this study are saprophytic conidia possibly from the soil and/or from broken or hair loss. This macroconidia might be a potential source of infection.